Edukasi dan Implementasi Pengelolaan Sampah Berbasis 3R (Reduce, Reuse, Recycle) di Kelurahan Lompo Riaja, Kecamatan Tanete Riaja, Barru - Sam’un Mukramin; Dicky Wahyudi; Muh. Akbar (Jurnal Informasi Pengabdian Masyarakat, 2025)
Public awareness and concern for waste is still very minimal, with this activity it is possible to increase public awareness of waste. To realize this goal, education and implementation of management in handling waste wisely are carried out. The aim is to reduce the negative impact of waste on the environment and public health. This activity focuses on implementation by providing education on 3R-based waste management (Reduce, Reuse, Recycle).